Investigating the prevalence rate of hypertension in Iranian men and women: A study of systematic review and meta-analysis - Yousof Mohsenzadeh; Morteza Motedayen; Farhad Hemmati; Kourosh Sayehmiri; Mohammad Taher Sarokhani; Diana Sarokhani (Journal of Basic Research in Medical Sciences, 2017)
Introduction: Based on the serious complications which are followed, hypertension is a common and asymptomatic health problem. This study aims to present a general statistics of the rate of the prevalence of systolic and diastolic hypertension in Iranian men and women based on the age range through the systematic review and meta-analysis method.